PENDAPATAN USAHA TANI JAGUNG HIBRIDA DI KECAMATAN BONTONOMPO SELATAN, KABUPATEN GOWA: Business Revenue In Hibrid Corn In Bontonompo District, South, Gowa District - Fajar Harianto; Abd. Asis Pata; Mohammad Anwar Sadat (Jurnal Agribis, 2019)
This study was conducted in South Bontonompo Subdistrict, Gowa Regency. Site was chosen on the consideration that do corn old farming hybrid.Data spoken there two are primary data: the data obtained from observations through interviews through the direct and also questions list and secondary data the data obtained from related agencies / institutions related or associated with this study.The purpose of this research is know: the farmers from corn hybrid farming income in South Bontonompo Subdistrict, Gowa Regency by observation field / observation. To get data used for the purpose of real analysis.This study a income in which use of income reduced the cost of counting the farmers from corn hybrid farming income in South Bontonompo Subdistrict, Gowa Regency. Research it can be seen farmers from the farming income obtained corn hybrid kecamatan south bontonompo kabupaten gowa is per Rp.7.606.450 once the growing season.